Ibn Barrajan's Sufistic Tafsir of Surah al-Baqarah and Ali Imran - Hafid, Moc; Yunus, Badruzzaman M.; Zulaiha, Eni; Muhyi, Asep Abdul (Program Studi Studi Agama-Agama Pascasarjana UIN Sunan Gunung Djati Bandung, 2024)
This study aims to know the Sufistic interpretation in Tafsir Tanbih and the characteristics of Tafsir Tanbih, which is focused on Surah al-Baqarah and Surah Ali Imran. Tafsir Tanbih is an eclectic collection/source of various materials collected over the years from various sources, Tafsir Tanbih is a Sufi interpretation of Ibn Barrajan trying to understand the meaning of every divine word with the teachings of Sufism, it can be seen from some interpretations of Surah al-Baqarah lafadz nazala 'alaikal litaaba bil haqqi, interpreted that this verse opens the door to a person's realization in himself through His asma in the lafad al-hayyu and al-Qayyum, someone who ma'rifat is who knows with a strong, perfect substance, and His sublime attributes, and His good names. The characteristics of Tafsir Tanbih are the experience of Mysticism and Spirituality in Tafsir Tanbih, using an Integrative approach in Tafsir Tanbih, there are Moral ideas in Tafsir Tanbih, there is a relationship with Ma'rifah (Divine Knowledge) in Tafsir Tanbih, understanding Mutashabihat Verses in Tafsir Tanbih. And many other characteristics.